Penggunaan Media Komik Fisika Berbasis Problem Solving Pada Materi Pemanasan Global Dalam Meningkatkan Motivasi Belajar dan Pemahaman Konsep Siswa - Nanda Safarati; Fatma Zuhra (Jurnal Penelitian Pendidikan IPA, 2023)
Learning media is an intermediary in the learning process, and is expected to arouse student motivation in learning activities, especially in physics lessons. However, some teachers have difficulty adapting the media to the material that will be provided, especially global warming material. So that causes a lack of interest in learning students to read textbooks, which results in a low understanding of students' concepts of physics subjects, especially on global warming material. The purpose of this study was to determine the increase in learning motivation and understanding of students' concepts through the use of problem solving-based physics comics on global warming material. The method used in this study is qualitative, a type of quasi-experimental research (quasi-experiment). The research design used was a two-group pretest-posttest design. Totaling 30 students selected by cluster random sampling. The instruments used in this study were test instruments (pretest-posttest) and non-test instruments (questionnaires). Data analysis shows the value of Sig. < 0.05, namely 0.00, thus Ho is rejected and Ha is accepted. It can be concluded that the use of problem solving-based physics comic media on global warming material can improve students' understanding of concepts.